Determination of chemical composition, gas production parameters and digestibility of leaves from several tree species (with and without polyethylene glycol) used in livestock feeding - Ruhollah Shahraki; javad bayatkouhsar; farzad Ghanbari; Abolfazl Daneshvar (پژوهشهای علوم دامی ایران, 2021)
Introduction[1]Lack of nutritional resources, especially in harsh conditions, is one of the major problems in the livestock and poultry industry. North of Iran due to its rich natural resources of native tree species and shrubs (50 tree and 80 shrubs) and annually significant amount of afforestation in cities, public places and natural areas, if they managed for animal feeding, can be an appropriate option for preparing a ration to feed the animals. Despite this capability, there is little information on the nutritional value of many tree and shrub species in the northern of the country. By targeting this approach in the researches, it is possible to manage natural resources and direct forestry to specific species. In this case, an effective step will be taken to manage the country's multifunctional forestry and it is also possible to diversify the countries livestock nutrition. The aim of this study was to determine the chemical composition, gas production parameters and detestability characteristics of leaves from several tree species used in livestock feeding in a Completely Randomized Design (7 treatments and 3 replicates).   Materials and Methods Samples of commonly available seven species of forest tree leaves (Siberian Elm, Lexandrian Laurel,Linden, Beech, Maple Tree, Caucasian oakand Hornbean) were collected from different locations of Shast-Klateh Forest of Golestan province, Gorgan. Gorgan is located in 36o 45´ N, 54o 21´ E. The mean annual rainfall is 649 mm. Samples were taken and air dried at 60 °C for 48 h and milled to pass a 1 and 1.5 mm screen. In this study, effects of adding polyethylene powder glycol (twice the weight of the sample, Merck, MW=6000) was evaluated. Their nutritional value was evaluated through determination of chemical compositions and in vitro gas production techniques. Samples were tested in an in vitro gas production method (96 h incubation) and batch rumen culture system (24 h incubation). Rumen fluid was collected before the morning feed from three fistulated Dalagh male sheep (43 ± 1.5 kg live weight fed on a forage diet at a concentration of 40:60). In vitro gas production was measured in triplicate and for each replicate, a sample of 200 mg DM were used. The bottles were then filled with 30 ml of incubation medium that consisted of 10 ml of rumen fluid plus 20 ml of buffer solution and placed in a water bath at 39 °C. Gas production was recorded at 2, 4, 8, 16, 24, 48, 72 and 96 h. Total gas values corrected for blank incubation and gas values expressed in ml g-1 of DM. The asymptotic gas production system (A) and rate of gas production (c), organic matter digestibility (OMD), metabolizable energy (ME) and short chain fatty acids (SCFA). A medium similar to one developed for gas production was used for batch rumen culture system to measure pH, and NH3-N and in vitro digestibility. The pH of the media was measured after 24 h incubation. After 24 h incubation, the contents of each glass bottle were empty, strained through four layers of cheesecloth and then 10 ml of strained rumen fluid was acidified by 10 ml of 0.2 N HCl for determination of NH3-N using the distillation method. Finally, all contents remaining in the bottles were filtered through nylon bags, oven dried at 60 °C for 48 h and analyzed for IVDMD and IVOMD.   Results and Discussion The results showed that the chemical composition of leaves of trees varied significantly among species. Maple tree had highest (1‏‏‏‏‏.27%) and Caucasian oak, Hornbean and Lexandrian Laurel had lowest (0‏‏‏‏‏.52, 0‏‏‏‏‏.56 and 0‏‏‏‏‏.58 respectively) of crude Ash content. The crude protein content of the tree leaves ranged from 7 to 18%. The highest and lowest tannin content were related to Beach tree (0‏‏‏‏‏.063 g‏‏‏‏‏/kg DM) and Caucasian oak (0‏‏‏‏‏.018 g‏‏‏‏‏/kg DM) respectively. There were significantly differences among several leaves of trees species on OMD, ME and SCFA. Addition of Poly Ethylene Glycol (PEG) increased potential gas production compared without PEG. The highest gas production and rate of gas production was related to Lexandrian Laurel tree without PEG (214‏‏‏‏‏/9 ml and 4‏‏‏‏‏.34 ml‏‏‏‏‏/h respectively). Portioning factor, Microbial crude protein and Gas yield decreased when used PEG.   Conclusion Generally, obtained results showed that some of the leaves of trees can be fed as supplements to low protein forage, and can alleviate feed shortage for ruminants in dry season.